2022
DOI: 10.1101/2022.08.02.22278277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-life evaluation of a rapid antigen test (DPP® SARS-CoV-2 Antigen) for COVID-19 diagnosis of primary healthcare patients, in the context of the Omicron-dominant wave in Brazil

Abstract: Rapid antigen tests play an important role in the monitoring and mitigation of the COVID-19 pandemic, as it provides an easy, fast and efficient diagnosis with minimum infrastructure requirements. However, as new variants of concern continue to emerge, mutations in the virus genome may impair the recognition of the mutated antigen by the tests. Therefore, it is essential to re-assess the test's sensitivity as the virus mutation profile undergoes significant changes. Here, we prospectively accessed the performa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Therefore, other diagnostic methods have been developed such as SARS-CoV-2 antigen detection via lateral flow testing, RT-LAMP, and CRISPR-based tests. However, recent studies evaluating the accuracy of diagnosis achieved by antigen LFT compared to RT-qPCR for primary care patients have shown that antigens-based tests are accurate for high viral load, but it generates uncertain and unreliable results in situations where the viral load is low 7,32 . Although the RT-LAMP and CRISPR-based methods have been demonstrated to be effective in detecting SARS-CoV-2, and their use has increased worldwide 8,10,11,13,[33][34][35] , these methods still require the use of enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other diagnostic methods have been developed such as SARS-CoV-2 antigen detection via lateral flow testing, RT-LAMP, and CRISPR-based tests. However, recent studies evaluating the accuracy of diagnosis achieved by antigen LFT compared to RT-qPCR for primary care patients have shown that antigens-based tests are accurate for high viral load, but it generates uncertain and unreliable results in situations where the viral load is low 7,32 . Although the RT-LAMP and CRISPR-based methods have been demonstrated to be effective in detecting SARS-CoV-2, and their use has increased worldwide 8,10,11,13,[33][34][35] , these methods still require the use of enzymes.…”
Section: Discussionmentioning
confidence: 99%